Expression of structural proteins and angiogenic factors in cerebrovascular anomalies - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2000)
OBJECTIVE: The goal of this study was to describe the expression of matrix proteins and angiogenic factors in cerebrovascular malformations. METHODS: Forty-six cerebrovascular malformations were immunohistochemically investigated with a battery of staining for five structural proteins (collagen IV collagen III, smooth muscle actin, fibronectin, and laminin), and three angiogenic factors (vascular endothelial growth factor [VEGF], basic fibroblast growth factor [bFGF], and transforming growth factor alpha[TGF alpha]). The lesions consisted of 34 arteriovenous malformations (AVMs), 10 cavernous malformations (CMs), and 2 venous angiomas. Expression intensity for each histological layer in the abnormal vessel wall was graded and compared. RESULTS: AVM endothelia and subendothelia expressed move laminin and collagen IV than the same layers of CMs. Conversely, CMs expressed move fibronectin than AVMs. CM endothelia exhibited more prominent staining for smooth muscle actin than AVM endothelia. AVMs and CMs expressed VEGF in the endothelium and subendothelium, and TGF alpha in endothelial and perivascular layers. However, unlike AVMs, CMs expressed bFGF in the endothelium as well. The brain tissue intermingled within AVMs also expressed growth factors. Modified glial cells in the brain tissue adjacent to CMs expressed bFGF and TGF alpha, but not VEGF. Venous angiomas did not express the studied growth factors and mainly consisted of structural proteins of angiogenically mature tissue. CONCLUSION: Expression characteristics of structural proteins reveal that AVMs and CMs have different immunohistological properties. This study provides strong confirmation of previous findings of VEGF and bFGF immunoexpression in AVMs and CMs. It adds new information on TGF alpha expression in these malformations and on expression of the angiogenic factors in venous angiomas.
Keywords: angiogenesis; arteriovenous malformation; cavernous malformation; fibroblast growth factor; fibronectin; laminin; structural proteins; transforming growth factor; vascular endothelial growth factor; venous angioma; ENDOTHELIAL GROWTH-FACTOR; VASCULAR-PERMEABILITY FACTOR; CEREBRAL ARTERIOVENOUS-MALFORMATIONS; INDUCED TRANSCRIPTIONAL ACTIVATION; SMOOTH-MUSCLE CELLS; CAVERNOUS MALFORMATIONS; EXTRACELLULAR-MATRIX; NATURAL-HISTORY; CAPILLARY TELANGIECTASIA; VENOUS MALFORMATIONS